STRATEGI DAN PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KUALITAS BELAJAR SISWA MATA PELAJARAN FIQIH DI MADRASAH ALIYAH NURUL HIDAYAH LEBAK JAHA - Ahmad Muflihuddin (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2021)
The purpose in this study is: (1) To describe the strategy of Islamic education teachers in improving the quality of student learning in Class XI Fiqh subjects at Madrasah Aliyah Nurul Hidayah Lebak Jaha (2) To describe the role the strategy of Islamic education teachers in improving the quality of student learning in Class XI Fiqh subjects at Madrasah Aliyah Nurul Hidayah Lebak Jaha (3) To know the strategies and roles of Islamic education teacher simultaneously to increases the quality of student learning in fiqh class XI Madrasah Aliyah Nurul Hidayah Lebak Jaha. The research approach used in this study is a qualitative by using the type of field research, to find out objectively the effectiveness of fiqh subject with the strategies and roles of Islamic education teachers in improving the quality of student learning. Data collection techniques used were interview, observation and documentation.The results of his research are: (1) The learning planning strategy of Islamic religious education teachers at Madrasah Aliyah Nurul Hidayah Lebak Jaha is well implemented; it includes the preparation of learning tools by creating syllabus and lesson plans based on curriculum content, in the learning process using expository strategies, and supported by the use of additional strategies, such as the strategy Inquiry Learn. (2) The teacher's role in increasing the quality of student learning in fiqh courses is to give assignments, punishments, praise, advise, and grades, all of which are carried out according to the learning evidence implementation plan of students with good character. (3) The teacher's strategies and roles have been successful in enhancing the quality of student learning, particularly in terms of how the teacher generates good competition in learning fiqh subjects. The way the teacher analyzes the learning process, including how the teacher creates a learning implementation strategy, leads learning to suit the plan, and how the instructor evaluates the learning process.